2009
DOI: 10.1179/14653120723256
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cranial base growth during pubertal growth

Abstract: Linear variables of cranial base showed significant growth during pubertal stages (pre-peak, peak and post-peak). No significant differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
2
9
0
3
Order By: Relevance
“…24 On the other hand, other studies showed slightly different growth rates in different age groups and suggested that cranial base growth was closely related to skeletal age. 20,27 Malta et al showed that the greatest amount of growth was 2.8 mm from time 1 to time 2, which correlated with CS1/2 change in growth to CS3/4. 27 Five studies showed size and growth differences between males and females as the cranial base dimensions increased, 24,25,28,32,36 whereas the other three studies indicated no difference according to sex.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…24 On the other hand, other studies showed slightly different growth rates in different age groups and suggested that cranial base growth was closely related to skeletal age. 20,27 Malta et al showed that the greatest amount of growth was 2.8 mm from time 1 to time 2, which correlated with CS1/2 change in growth to CS3/4. 27 Five studies showed size and growth differences between males and females as the cranial base dimensions increased, 24,25,28,32,36 whereas the other three studies indicated no difference according to sex.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…20,27 Malta et al showed that the greatest amount of growth was 2.8 mm from time 1 to time 2, which correlated with CS1/2 change in growth to CS3/4. 27 Five studies showed size and growth differences between males and females as the cranial base dimensions increased, 24,25,28,32,36 whereas the other three studies indicated no difference according to sex. 26,27,31 Two studies reported changes in S-Ba length in adulthood.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations